(untitled) (Research, Society and Development, 2020)
The article aims to understand the structuring of schoolwork for autistic students in a Special Education School, in the Northern State of Paraná. Thereunto, it also debates Public Policies focused on Autistic Spectrum Disorder (TEA) and its main characteristics. Through qualitative and field research, with semi-structured interviews, it analyzes how school work is structured, the care provided by the multidisciplinary team, and the role played by the family in the child’s teaching and learning process. The study showed that Inclusive Educational Policies have advanced regarding TEA rights, whether in the school or social context. The State of Paraná stands out for its pioneering spirit and the expansion of discussions and proposals in this type of teaching. However, there is a long way to go in the face of difficulties and barriers in the process of teaching and learning these students. In the case under analysis, the work carried out by the multi-professional team is still in constant adaptation to the student, as not all professionals have suitable methodologies, materials for differentiated pedagogical practices, and especially specific professional training in the work with TEA are lacking.